The Backyard of EFL Teaching: Issues Behind L1 Prosodic Interference in Russian English - Ekaterina Popkova (National Research University Higher School of Economics, 2015)
Modern EFL teaching in Russia pays much attention to variations in the cultural schemata represented by students' L1 and the target language, as well as behavioral patterns of their speakers. However, teaching practitioners scarcely address certain issues of Russian L1 prosodic interference that cause attitudinal confusion on the part of native English speakers. The study explores the wrong pragmatic effects created in English due to the transfer of Russian intonation contours and the reasons behind the failure of Russian EFL teachers to address the issue. Specifically, it investigates English speakers' negative perceptions of Russian L1 intonation and examines Russian teachers' practices and beliefs with regard to the place of intonation in a language classroom. The paper draws on findings from recent studies on effects of Russian L1 prosodic features in English and the results obtained from a survey conducted by the author among 29 Russian EFL teachers. The paper argues that whereas L1 intonation interference seriously affects learners' cultural image, its role in EFL teaching is significantly undervalued as compared to that of grammar and vocabulary. It concludes by suggesting practical ways to facilitate intonation teaching in a Russian EFL classroom.